Preference of teaching and learning methods in a new medical school of Malaysia - Salwani Ismail, Nor Iza A Rahman, Nasir Mohamad, Norhasiza Mat Jusoh, Aminatul Izzah Binti Hood, Liyana Aqilah Binti Arif, Wan Siti Aishah Binti Wan Abdullah, Zetty Nasfariza Binti Zainal, Md. Zakirul Islam, Wan Putri Elena Wan Dali, Mainul Haque (Journal of Applied Pharmaceutical Science, 2014)
Teaching and learning are the two sides of a coin. Henceforth, there is a strong correlation between the methods used in delivering the information by the lecturers and the assimilation of that knowledge by the students. MBBS programme of FPSK, UniSZA, is divided into two phases, preclinical (Year I and II) and clinical (Year III, IV and V) phases. The main teaching and learning methods for preclinical phase include lecture, tutorial, practical, problem based learning (PBL) and early clinical exposure (ECE). This cross-sectional study was conducted in July 2013 in UniSZA, Malaysia. 50 respondents from preclinical phase were randomly selected from total 117 students to answers the questionnaire. The questionnaire was developed with extensive literature review and pretested and validated. The questionnaire has been divided into 5 sections. The data were analysed using the SPSS 17.0. This study showed that 36 (72%) out of 50 respondents chose lecture as the most preferred teaching and learning method. Five (10%) out of 50 respondents preferred tutorial and 3 (6%) out of 50 respondents preferred PBL, practical and ECE respectively. None of the respondents chose Computer Assisted Learning (CAL) as a preferred method. Probably learning guideline of CAL is not clear that make the session the most un-preferred. Majority of the students in preclinical phase preferred lecturer/teacher-centred learning session to acquire knowledge in a medical school.
Keywords: Preference,Teaching,Learning Methods,Medical School,Malaysia.